The Implementasi Kurikulum Merdeka Belajar dalam Pembelajaran Bahasa Arab - Fitri Masturoh; Ihwan Mahmudi (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
The research aims to determine the implementation of the Merdeka Belajar curriculum in learning Arabic and the strategies used in implementing the of the Merdeka Belajar curriculum in learning Arabic at SMP Terpadu Darussalam Rajapolah Tasikmalaya. The research method used descriptive qualitative research with data collection techniques using documentation, observation, and interviews. The result of research that:1) Arabic language learning at SMP Terpadu Darussalam has been implemented and adapted to the implemented curriculum, which combines the curriculum of the Ministry of Education and Culture, KMI Gontor, Salafiyah and tahfidz Al-Qur'an which supports the achievement of learning Arabic. 2)The implementation of the Merdeka Belajar in learning Arabic at SMP Terpadu Darussalam includes several programs, namely; Arabic National Seminar for Teachers, formation of student organizations in the language section, the effectiveness of learning Arabic in the classroom and outside the classroom, in the classroom includes learning group subjects at lughawiyah with the direct method as well as learning methods and models based on the independent curriculum, outside the classroom namely extracurricular activities including muhāḍarah, muhādaṡah, musyāhadah al-aflām al-arābiyah, mahkāmah  al-lughah, arabic drama contest, as well as internal and external competition activities.